Characterization of interaction of magnetic nanoparticles with breast cancer cells - VOLKOV, YURI (My University, 2015)
Background Different superparamagnetic iron oxide nanoparticles have been tested for their potential use in cancer treatment, as they enter into cells with high effectiveness, do not induce cytotoxicity, and are retained for relatively long periods of time inside the cells. We have analyzed the interaction, internalization and biocompatibility of dimercaptosuccinic acid-coated superparamagnetic iron oxide nanoparticles with an average diameter of 15 nm and negative surface charge in MCF-7 breast cancer cells. Results Cells were incubated with dimercaptosuccinic acid-coated superparamagnetic iron oxide nanoparticles for different time intervals, ranging from 0.5 to 72 h. These nanoparticles showed efficient internalization and relatively slow clearance. Time-dependent uptake studies demonstrated the maximum accumulation of dimercaptosuccinic acid-coated superparamagnetic iron oxide nanoparticles after 24 h of incubation, and afterwards they were slowly removed from cells. Superparamagnetic iron oxide nanoparticles were internalized by energy dependent endocytosis and localized in endosomes. Transmission electron microscopy studies showed macropinocytosis uptake and clathrin-mediated internalization depending on the nanoparticles aggregate size. MCF-7 cells accumulated these nanoparticles without any significant effect on cell morphology, cytoskeleton organization, cell cycle distribution, reactive oxygen species generation and cell viability, showing a similar behavior to untreated control cells. Conclusions All these findings indicate that dimercaptosuccinic acid-coated superparamagnetic iron oxide nanoparticles have excellent properties in terms of efficiency and biocompatibility for application to target breast cancer cells.
PUBLISHED
Keywords: MCF-7 cells; Superparamagnetic iron oxide nanoparticles; Intracellular trafficking; Transmission electron microscopy; Cellular uptake; Endocytosis; Cytotoxicity; MCF-7 cells; Superparamagnetic iron oxide nanoparticles; Intracellular trafficking; Transmission electron microscopy; Cellular uptake; Endocytosis; Cytotoxicity